P2Y12 Receptor Antagonist Clopidogrel Attenuates Lung Inflammation Triggered by Silica Particles - Santana, Patricia Teixeira; Luna-Gomes, Tatiana; Rangel-Ferreira, Marcos Vinicius; Tamura, Augusto Shuiti; Da Graça, Carolyne Lalucha Alves Lima; Machado, Mariana Nascimento; Zin, Walter Araujo; Takiya, Christina Maeda; Faffe, Debora Souza; Coutinho-Silva, Robson (Frontiers in Pharmacology, 2020)
Silicosis is an occupational lung disease caused by inhalation of silica particles. It is characterized by intense lung inflammation, with progressive and irreversible fibrosis, leading to impaired lung function. Purinergic signaling modulates silica-induced lung inflammation and fibrosis through P2X7 receptor. In the present study, we investigate the role of P2Y12, the G-protein-coupled subfamily prototype of P2 receptor class in silicosis. To that end, BALB/c mice received an intratracheal injection of PBS or silica particles (20 mg), without or with P2Y12 receptor blockade by clopidogrel (20 mg/kg body weight by gavage every 48 hours) - groups CTRL, SIL, and SIL+Clopi, respectively. After 14 days, lung mechanics were determined by the end-inflation occlusion method. Lung histology was analyzed, and lung parenchyma production of nitric oxide and cytokines (IL-1β, IL-6, TNF-α, and TGF-β) were determined. Silica injection reduced animal survival and increased all lung mechanical parameters in relation to CTRL, followed by diffuse lung parenchyma inflammation, increased neutrophil infiltration, collagen deposition and increased pro-inflammatory and pro-fibrogenic cytokine secretion, as well as increased nitrite production. Clopidogrel treatment prevented silica-induced changes in lung function, and significantly reduced lung inflammation, fibrosis, as well as cytokine and nitrite production. These data suggest that inhibition of P2Y12 signaling improves silica-induced lung inflammation, preventing lung functional changes and mortality. Our results corroborate previous observations of silica-induced lung changes and expand the understanding of purinergic signaling in this process.